2011
DOI: 10.1021/ja2036749
|View full text |Cite
|
Sign up to set email alerts
|

Luminscent Graphene Quantum Dots for Organic Photovoltaic Devices

Abstract: Recent research in organic photovoltaic (OPV) is largely focused on developing low cost OPV materials such as graphene. However, graphene sheets (GSs) blended conjugated polymers are known to show inferior OPV characteristics as compared to fullerene adduct blended with conjugated polymer. Here, we demonstrate that graphene quantum dots blended with regioregular poly(3-hexylthiophene-2,5-diyl) or poly(2-methoxy-5-(2-ethylhexyloxy)-1,4phenylenevinylene) polymer results in a significant improvement in the OPV ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
628
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 895 publications
(644 citation statements)
references
References 29 publications
13
628
0
3
Order By: Relevance
“…The Raman spectroscopy of the GQDs (Fig. 1b) shows the partially disordered crystal structure of GQDs that the scattering at the edges caused [29].…”
Section: Resultsmentioning
confidence: 99%
“…The Raman spectroscopy of the GQDs (Fig. 1b) shows the partially disordered crystal structure of GQDs that the scattering at the edges caused [29].…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that graphene quantum dots (GQDs) blended with P3HT resulted in a significant improvement in PSC characteristics compared to graphene sheets blended with conjugated polymers. 15 However, the obtained PCE for the GQDs-based PSC was rather low (B1%). Here, we show that for PSC applications, light-emitting GQDs derived from doublewalled carbon nanotubes (DCNTs) can be used as an excellent supplement to P3HT:PCBM, rather than a replacement.…”
Section: Introductionmentioning
confidence: 94%
“…This is mainly because CNTs have poor solubility in organic polymer matrices and wide distributions in lengths and diameters. [171][172][173][174][175] Graphene has the advantage of higher electron mobility than that of C 60 derivatives as well as energy levels easily tunable by adjusting the material's size and functionality. Furthermore, graphene's large specific surface area and 2D structure favor the formation of a bicontinuous interpenetrating network of donor and acceptor at nanometer scale with maximum interfacial area.…”
Section: Heterojunction Solar Cellsmentioning
confidence: 99%